2016
DOI: 10.1007/s00284-016-1085-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Probiotic SYNBIO® Administered by Vaginal Suppositories in Promoting Vaginal Health of Apparently Healthy Women

Abstract: The purpose of this study was to investigate whether vaginal administration of probiotic Lactobacillus results in their colonization and persistence in the vagina and whether it promotes normalization and maintenance of pH and Nugent score. A single-arm, open-label controlled towards the baseline (pre-post) study including 35 apparently healthy women was conducted. Each woman was examined three times during the study. Women were instructed to receive daily for 7 days, the probiotic suppositories SYNBIO(®) gin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 33 publications
3
31
0
Order By: Relevance
“…The search identified 2949 unique articles but only 34 studies were eligible (flow diagram in Figure ) . Thirteen studies reported 14 results on BV and/or molecular VMB composition (Table ), 12 studies reported 12 results on VVC (Table ), and 14 studies reported 15 results on vaginal probiotic strain detection using molecular techniques (Table S1). The selected studies evaluated 22 different vaginal probiotics (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search identified 2949 unique articles but only 34 studies were eligible (flow diagram in Figure ) . Thirteen studies reported 14 results on BV and/or molecular VMB composition (Table ), 12 studies reported 12 results on VVC (Table ), and 14 studies reported 15 results on vaginal probiotic strain detection using molecular techniques (Table S1). The selected studies evaluated 22 different vaginal probiotics (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported 14 results on BV and/or molecular VMB composition (Table ), 12 studies reported 12 results on VVC (Table ), and 14 studies reported 15 results on vaginal probiotic strain detection using molecular techniques (Table S1). The selected studies evaluated 22 different vaginal probiotics (Table S2). The most studied were Gynoflor ( L. acidophilus KS400 plus 30 microgram oestriol; three studies with 359 participants), Lactin‐V ( L. crispatus CTV‐05; four studies with 132 participants), and L. reuteri RC‐14 with L. rhamnosus GR‐1 (four studies with 47 participants).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, vaginal suppositories containing L. rhamnosus IMC 501 and L. paracasei IMC 502 were tested in apparently healthy women. The authors registered 40% of patients with an intermediate Nugent score before the treatment and half of them returned to a normal state (low Nugent score) after the intervention [132]. Besides, when compared to placebo, vaginal capsules of L. fermentum 57A, L. plantarum 57B and L. gasseri 57C were able to significantly reduce vaginal pH and Nugent score, suggesting a shift to a healthy vaginal microbiota profile.…”
Section: Probiotics and Microbiota Manipulationmentioning
confidence: 97%
“…The probiotic group had significantly lower incidence of discharge than metronidazole group (P = 0.024) and higher cure rate than metronidazole group, but this difference was not significant (P = 0.269). Verdenelli et al (2016) evaluated the effect of probiotic suppositories, SYNBIO® gin, on vaginal health. The study included 35 apparently healthy women (aged 18-48 years), who were instructed to receive daily for 7 days the probiotic suppositories SYNBIO® gin, containing at least 10 9 CFU of viable lactobacilli, a combination of L. rhamnosus IMC 501® and L. paracasei IMC 502®.…”
Section: Intravaginal Administration Of Probioticsmentioning
confidence: 99%